2019
DOI: 10.1002/jsid.825
|View full text |Cite
|
Sign up to set email alerts
|

Alignment control technology of liquid crystal molecules

Abstract: Liquid crystal displays are now indispensable in everyday life. The display characteristics considerably depend on the configuration of liquid crystal (LC) molecules and interactions between the LC molecules and an alignment film surface. In this paper, we introduce various methods to control parameters that dominate the LC alignment. These parameters include order parameters, the pretilt angle, the director direction, and surface anchoring strength. We also introduce their evaluation methods. In particular, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 179 publications
(305 reference statements)
1
34
0
Order By: Relevance
“…The capacitance C ⊥ was then calculated by taking φ a = 2 • in Eqs. (10) and (12) and the dielectric constants ⊥ and were calculated by dividing C ⊥ and C by the capacitance C 0 of the empty cells. From these measurements the dielectric anisotropy a and the factor γ were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The capacitance C ⊥ was then calculated by taking φ a = 2 • in Eqs. (10) and (12) and the dielectric constants ⊥ and were calculated by dividing C ⊥ and C by the capacitance C 0 of the empty cells. From these measurements the dielectric anisotropy a and the factor γ were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Such surface treatments exist but we did not have them. We can cite, for instance, the surface treatment by deposition under oblique incidence of a layer of SiO, at least under certain conditions [36], or certain treatments with photopolymers [12]. This method also requires to have an adequate polymer to obtain a strong homeotropic anchoring, which was the case with 8CB and the mixture 8CB-CB7CB used in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the vertical orientation of nematic LCs, wherein the director of the nematic LCs is oriented vertically to the surface of the substrate, has been studied for sensor applications because of its susceptibility to small perturbations and binding events [ 15 , 16 , 17 , 18 ], which can be observed by an optical apparatus such as a polarized optical microscopy (POM) [ 19 , 20 ]. It has been demonstrated that LC molecules can be aligned by the anisotropic characteristics of a surface via numerous contact and noncontact methods, such as mechanical rubbing, stretching, lithography, polarized ultraviolet (UV) radiation, and ion beam treatment [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Among these, the mechanical rubbing of polymeric surfaces is the most commonly used contact method to obtain a uniform orientation of LC molecules because of its simplicity and rapidity [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] In the early stage LCD technology, LCs exhibiting twisted nematicity (TN) show better performance in LCD technology and many devices are still using TN–LCDs nowadays due to its fast response time. [ 14 ] In a TN–LCD, the nematic LC layer exists in a twisted or helical configuration between perpendicular alignment layers.…”
Section: Introductionmentioning
confidence: 99%